A Downsized and Optimised Intracellular Library-Derived Peptide Prevents Alpha-Synuclein Primary Nucleation and Toxicity Without Impacting Upon Lipid Binding. Issue 24 (3rd December 2021) - Meade, Richard M.; Watt, Kathryn J.C.; Williams, Robert J.; Mason, Jody M.
Graphical abstract: Highlights: Synucleinopathies are caused by aggregation of the protein alpha-Synuclein (aS) The PreNAC region implicated in early onset PD serves as a peptide library template. Ala scans result in a shorter modified peptide of significantly increased efficacy. 4654(N6A) prevents aS primary nucleation and toxicity but not lipid binding. Abstract: Misfolding and aggregation of alpha-synuclein (αS) within dopaminergic neurons is a key factor in the development and progression of a group of age-related neurodegenerative diseases, termed synucleinopathies, that include Parkinson's disease (PD). We previously derived a peptide inhibitor from a 209, 952-member intracellular library screen by employing the preNAC region (45–54) as a design template. At least six single-point mutations firmly linked to early-onset Parkinson's disease (E46K, H50Q, G51D, A53T/E/V) are located within this region, strongly implicating a pathogenic role within αS that leads to increased cytotoxicity. A library-derived ten residue peptide, 4554W, was consequently shown to block αS aggregation at the point of primary nucleation via lipid induction, inhibiting its conversion into downstream cytotoxic species. Here we couple truncation with a full alanine scan analysis, to establish the effect upon the αS aggregation pathway relative to 4554W. This revealed the precise residues responsible for eliciting inhibitory interaction and function, as well as those potentially amenable to modification or functionalisation. We find that modification N6A combined with N-terminal truncation results in a peptide of significantly increased efficacy. Importantly, our data demonstrate that the peptide does not directly disrupt αS lipid-binding, a desirable trait since antagonists of αS aggregation and toxicity should not impede association with small synaptic neurotransmitter vesicles, and thus not disrupt dopaminergic vesicle fusion and recycling. This work paves the way toward the major aim of deriving a highly potent peptide antagonist of αS pathogenicity without impacting on native αS function.